Geological Mapping of the Longkeyang and Surrounding Regions, Bodeh District, Pemalang Regency, Central Java - Firmansyah, Irwan; Candra, Adi; Widiatmoko, Fajar Rizki (Journal of Earth and Marine Technology (JEMT), 2021)
Geological mapping is one of the important things as part of a field study to obtain geological knowledge. This is due to the need for a geologist who is required to be able to understand the geological conditions of an area, one of which is by conducting mapping activities in the field. In conducting this research activity, it is divided into two stages, namely the field stage and the laboratory stage. The purpose of this research is to determine the characteristics and geological conditions, identify resource potentials and potential geological disasters in the research area. Based on the analysis, it was found that the geomorphological units of the study area were divided into 4 (four), namely the Mount Ketos Homocline Hills Unit, the Polaga River Anticline Valley Unit, the Sarangkadu Cycline Hills Unit, and the Mount Lanji Intrusion Hills Unit. The geology of the study area consists of three rock units in order from oldest to youngest, namely the claystone-sandstone unit and the sandstone-claystone unit and the diorite intrusion unit. The geological structure of the pinnacle area is in the form of folds and faults, namely, Polaga River Anticlines, Sarangkadu Synclines, Polaga River Right Shear Fault, Polaga River Left Shear Fault. The geological history of the study area begins with the deposition of claystone-sandstone units during the Middle Miocene in the Upper Bathyal environment. Furthermore, after the claystone-sandstone units were deposited, during the Middle Miocene – Late Miocene in the Deep Neuritic environment, sandstone-claystone units were deposited with a turbidity deposition mechanism. As well as the geological resource potential of the research area in the form of utilization of river deposits in the form of chunks of igneous rock, river sand deposits and indications of the presence of gold. Meanwhile, the potential for geological disasters in the form of landslides.